Making semantics pragmatic - Turner, Ken, 1956- (Bingley, U.K. : Emerald, 2011)
This collection of especially invited papers aims to explore the nature of the semantics/pragmatics interface by examining the extent to which the analysis of certain expressions or constructions can be pragmaticised. As the title of the collection implicates, it is anticipated that the theoretical and descriptive burden will move from semantics to pragmatics. However not all parts of a linguistic system will yield to a pragmatic treatment. The possibility remains that certain expressions or constructions are more economically and elegantly treated in semantic terms. Thus, this collection also contains papers that address the topic of making pragmatics semantic. This collection contributes to the current interest in examining the division of labour between semantics and pragmatics in the analysis of meaning. All of the papers areat the forefront of knowledge in these matters and each contains original empirical analyses and/or novel theoretical perspectives. The book is relevant to courses in university departments of linguistics, modern languages, philosophy and psychology and to a wide range of university teaching and research.
1. Introduction : preliminary'sketches of landscapes' / Ken Turner -- 2. Whatever happened to meaning? : remarks on contextualisms and propositionalisms / Jay David Atlas -- 3. What refers? How? / Alex Barber -- 4. Bearers of truth and the unsaid / Stephen Barker -- 5. Towards a radically pragmatic theory of if-conditionals / Gunnar Bj$1'Xr(Bnsson -- 6. French relational words, context sensitivity and implicit arguments / Brendan S. Gillon -- 7. Mutual manifestness and the pragmatic marker Ne / Marita Ljungqvist -- 8. The use-theory of meaning and the rules of our language games / Jaroslav Peregrin -- 9. Say what / Ian Ross.s
Includes index.
Keywords: Semantics; Pragmatics